Effect of engineered lattice contraction and expansion on the performance and CO2 tolerance of Ba0.5Sr0.5Co0.7Fe0.3O3-δ functional material for intermediate temperature solid oxide fuel cells. Issue 15 (1st August 2022) - Bello, Idris Temitope; Yu, Na; Zhai, Shuo; Song, Yufei; Zhao, Siyuan; Cheng, Chun; Zhang, Zhenbao; Ni, Meng
Abstract: Barium Strontium Cobalt Iron Oxide (BSCF) is a famous cathode material for solid oxide fuel cells (SOFCs) due to its excellent catalytic activity for oxygen reduction reaction (ORR) at intermediate and low operating temperatures. Its poor stability, however, in a CO2 -containing environment limits its practical application. In this study, we systematically investigate the effects of instigating lattice contraction and expansion on the performance and CO2 tolerance of Ba0.5 Sr0.5 Co0.7 Fe0.3 O3-δ (BSCF) air electrode functional material. We strategically substituted 5 mol.% Fe–B-site cations of BSCF with transition metals (TMs), i.e., Zn and Cu, to achieve lattice expansion and contraction, respectively. The Ba0.5 Sr0.5 Co0.7 Fe0.25 Cu0.05 O3-δ (BSCFC5) cathode, where lattice contraction occurred, exhibits the best performance with an area-specific resistance (ASR) of 0.0247 Ω cm 2 and a high peak power density (PPD) of 1715 mW cm −2 at 650 °C for the symmetrical and single cells, respectively. The functional material also exhibits enhanced tolerance to CO2 compared to BSCF by surviving several rounds of 10% CO2 injection and ejection for an overall nonstop testing period of 100 h. The improved ORR, stability, and CO2 tolerance instigated by lattice contraction in BSCF provides an insight into the adoption of this approach in achieving optimal desirable properties in SOFC cathode functional materials. Graphical abstract: Image 1